Malyngamide F Possesses Anti-Inflammatory and Antinociceptive Activity in Rat Models of Inflammation - Zhuocheng Li; Lei Zhang; Zhichao Zhao (Pain Research and Management)
Objective. Inflammation and pain are involved in the pathophysiology of various clinical conditions. This investigation aims to probe the analgesic and anti-inflammatory activity of Maltoamide F. Methods. The possible toxicity of Maltoamide F was evaluated by an acute toxicity test. To assess the anti-inflammatory and antinociceptive effects of Maltoamide F on rats, the models of carrageenan-caused paw edema, xylene-induced ear edema, arachidonic-acid- (AA-) induced ear edema, formalin-caused plantar edema, and cotton-pellet-induced granuloma were established. Levels of TNF-α, PGE-2, and IL-6 were detected by enzyme-linked immunosorbent assay (ELISA). Results. Maltoamide F was safe at oral doses of 1–10 mg/kg for rats. Maltoamide F (1 mg/kg, 5 mg/kg, and 10 mg/kg) notably reduced carrageenan-induced edema percentage of paws in rats and decreased levels of PGE-2, IL-6, and TNF-α in homogenates of foot tissues. Maltoamide F (1 mg/kg, 5 mg/kg, and 10 mg/kg) reduced levels of PGE-2, IL-6, and TNF-α in foot tissues of formalin-induced rats. Maltoamide F (1 mg/kg, 5 mg/kg, and 10 mg/kg) repressed AA-induced increase of ear thickness in rats and reduced levels of PGE-2, IL-6, and TNF-α in homogenates of ear tissues. Maltoamide F (1 mg/kg, 5 mg/kg, and 10 mg/kg) reduced xylene-induced weight of ear edema in rats and reduced levels of PGE-2, IL-6, and TNF-α in homogenates of ear tissues. Maltoamide F (1 mg/kg, 5 mg/kg, and 10 mg/kg) reduced levels of PGE-2, IL-6, and TNF-α in homogenates of cotton ball granuloma of cotton-pellet-induced rats. Conclusions. Maltoamide F possessed anti-inflammatory and analgesic activity in inflammatory models of rats.